2018
DOI: 10.1016/j.quascirev.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation history and human-environment interactions through the late Holocene in Konar Sandal, SE Iran

Abstract: The Jiroft valley, situated on banks of the Halil Rud developed as an important agricultural and trading center during the Early Bronze Age. Known for its famous steatite sculptures and clay pottery, the first settlement in Konar Sandal collapsed around 3rd millennium BCE. A second shorter, but major phase of occupation in the settlement occurred towards the end of 2nd millennium BCE. A 250-cm long peat sequence near the archaeological complex at Konar Sandal was investigated to reconstruct the humanenvironmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Multiproxy investigation of lake core sediments is a prerequisite for reconstruction and a proper understanding of the high-resolution paleoclimate/paleoenvironmental variability (Ali et al, 2018; An et al, 2012a, 2012b; Hillman et al, 2018; Lauterbach et al, 2014; Lei et al, 2014; Ning et al, 2017; Sandeep et al, 2017; Schwarz et al, 2017), lacustrine regime shifts (Hembrow et al, 2018; Liiv et al, 2018; Liu et al, 2013), and human impacts (Gurjazkaite et al, 2018; Hillman et al, 2018; Niemann et al, 2013; Ohlendorf et al, 2003; Zhang et al, 2014) spanning the Holocene period (since ~11,700 yr BP). Variability in the proxy records of lake sediments is characterized by sudden and persistent responses to climate-induced environmental changes over the catchment areas, including precipitation and temperature changes, anthropogenic influences, and primary productivity among others (Hillman et al, 2018; Schwarz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Multiproxy investigation of lake core sediments is a prerequisite for reconstruction and a proper understanding of the high-resolution paleoclimate/paleoenvironmental variability (Ali et al, 2018; An et al, 2012a, 2012b; Hillman et al, 2018; Lauterbach et al, 2014; Lei et al, 2014; Ning et al, 2017; Sandeep et al, 2017; Schwarz et al, 2017), lacustrine regime shifts (Hembrow et al, 2018; Liiv et al, 2018; Liu et al, 2013), and human impacts (Gurjazkaite et al, 2018; Hillman et al, 2018; Niemann et al, 2013; Ohlendorf et al, 2003; Zhang et al, 2014) spanning the Holocene period (since ~11,700 yr BP). Variability in the proxy records of lake sediments is characterized by sudden and persistent responses to climate-induced environmental changes over the catchment areas, including precipitation and temperature changes, anthropogenic influences, and primary productivity among others (Hillman et al, 2018; Schwarz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A slight increase in terrigenous input is observed in this area which is contemporaneous to the optimum climate of the Iranian plateau and Near East (Bar-Matthews et al 2003;Frumkin et al 1991). Vaezi et al (2018) showed a decrease in aeolian input together with an abrupt increase in rainfall between 5 and 4.7 cal kyr BP in the Hamun-e Jazmurian basin, about 140 km northeast of the SH. This optimal climate caused the flourishment of Bronze Age civilizations from Mesopotamia toward SE Iran and is attributed to the ISM-induced precipitations (Fleitmann et al 2007;Cullen et al 2000).…”
Section: Unit A: ~5000 -4300 Cal Yr Bpmentioning
confidence: 74%
“…This significant warming is also documented in the Near East by a prolonged drought (Issar 2004). The high aeolian input, high salinity, and rise in evaporite minerals were detected around 4.3 cal kyr BP in lake sediments of Hamun-e Jazmurian suggesting a dry condition (Vaezi et al 2018). At the same time, Bronze Age civilization in the southeast and east of Iran evanesced.…”
Section: Unit A: ~5000 -4300 Cal Yr Bpmentioning
confidence: 99%
“…However, most of these studies have focused on lacustrine basins located further to the south/southwest of Fars province, with so far no palaeo-environmental records from the Pasargadae region itself. On a broader scale, high-resolution palaeo-environmental reconstructions are more numerous for the northern Zagros (Wasylikowa et al, 2008), northwestern Iran and eastern Anatolia (Sharifi et al, 2015), and southeast Iran (Hamzeh et al, 2016;Gurjazkaite et al, 2018;Vaezi et al, 2019;Safaierad et al, 2020). As regards these studies, the general postglacial hydro-climatic changes followed global trends, with glacial retreat and expansion of woodlands at the expense of open steppe landscapes.…”
Section: Changes In Holocene Hydrology and Vegetation In Farsmentioning
confidence: 99%